Complicaciones tempranas en la artroplastia total primaria de la cadera. Experiencia Hospital de San José, Bogotá 2000-2005 (2006)
Actually, total hip arthroplasty is one of the most frequent procedures in orthopedic surgery. Without concerning the used technique it still has complications. This can be early (in to the fi rst three months) or late complications (after the fi rst three months). In Our institution we haven’t studies that show the incidence of early complications in primary total hip arthroplasty. Patients and methods: It is a descriptive observational retrospective study, we included 315 patients with 337 hip prostheses from 426 total hip arthroplasties performed between January 2000 to September 2005 followed at least for three months. We include demographic data, and the early complications incidence was made using measures of central tendency. Results: 315 patients, in 22 a bilateral procedure was made (44 hips), 293 were unilateral. 68.5% women, 56.4% right hips, and the mean age was 58.26 years (19-90). Development hip dysplasia was the most prevalent diagnosis (73%), early instability, the most frequent complication (3, 6%). Deep vein thrombosis was detected in 2,7% of patients. Infection was present in 1.8% of the patients; two of them a second procedure because of it. Conclusions: We observe similarity in the frequency of complications between patients treated in our hospital and those reported in the orthopedic literature, except in deep vein thrombosis that was higher, probably because the poor adherence to prophylaxis observed in our patients. Instability was found in 3.6%, being this inferior to the international reports, considering that the approach type used in our institution is posterolateral.